Assessment of antitussive efficacy of dextromethorphan in smoking related cough: objective vs. subjective measures - Ramsay, James (Blackwell Science Inc, 2008)
AIMS: Using an established model of smokers cough we measured the antitussive effects of dextromethorphan compared with placebo. METHODS: The study was a randomized, double-blind placebo controlled, crossover comparison of 22 mg 0.8 ml(−1) dextromethorphan delivered pregastrically with matched placebo. Objective and subjective measurements of cough were recorded. Subjective measures included a daily diary record of cough symptoms and the Leicester quality of life questionnaire. Cough frequency was recorded using a manual cough counter. The objective measure of cough reflex sensitivity was the citric acid, dose–response cough challenge. RESULTS: Dextromethorphan was significantly associated with an increase in the concentration of citric acid eliciting an average of two coughs/inhalation (C2) when compared with placebo, 1 h post dose by 0.49 mM (95% CI 0.05, 0.45, geometric mean 3.09) compared with placebo 0.24 mM (geometric mean 1.74) P < 0.05 and at 2 h 0.57 mM (95% CI 0.01, 0.43, geometric mean 3.75) compared with placebo 0.34 mM (geometric mean 2.19) P < 0.05). There was a highly significant improvement in the subjective data when compared with baseline. However, there was no significant difference between placebo and active treatment. No correlation was seen between cough sensitivity to citric acid and recorded cough counts or symptoms. When both subjective and objective data were compared with screening data there was evidence of a marked ‘placebo’ effect. CONCLUSIONS: The objective measure of cough sensitivity demonstrates dextromethorphan effectively diminishes the cough reflex sensitivity. However, subjective measures do not support this. Other studies support these findings, which may represent a profound sensitivity of the cough reflex to higher influences.